Ocean Dynamics - Ocean Dynamics (Springer Nature, 2026)
Ocean Dynamics is an international journal that aims to publish high-quality peer-reviewed articles in the following areas of research: Theoretical oceanography (new theoretical concepts that further system understanding with a strong view to applicability for operational or monitoring purposes). Computational oceanography (all aspects of ocean modeling and data analysis). Observational oceanography (new techniques or systematic approaches in measuring oceanic variables, including all aspects of monitoring the state of the ocean). Articles with an interdisciplinary character that encompass research in the fields of biological, chemical and physical oceanography are especially encouraged.
FI 0.8
Q2
Keywords: Earth; Space & Environmental Sciences; Oceanography & Paleoceanography; Oceanografía; Paleoceanografía; Acuerdos transformativos; Transformative agreements; Oceanografía teórica; Oceanografía biológica, química y física